Exploring the English-speaking Landscape : A Typology of Vulnerability Associated with Employment in Quebec's English-speaking Population - Warnke, Jan; Bolger, Laura-Lee (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This exploratory study uses geodemographic analytical methods to investigate the English-speaking population of Quebec, with a specific focus on vulnerability indicators associated with employment and their spatial distribution within the province. Using Ward’s cluster analysis method, eight distinct groups were identified and mapped, each showcasing unique characteristics that warrant tailored policy measures to effectively tackle regional employment challenges. Future research should delve into the differential impacts of various variables across clusters, particularly those related to mobility and aboriginal identity, thereby facilitating the derivation of targeted policy interventions.

Employment of English Speakers in Quebec's Public Service - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
This document provides background information related to the participation of English speakers in Quebec’s Public Service (QPS). The first section synthesizes information from relevant primary and secondary sources. The second section includes summaries of preliminary discussions with key informants, as well as our observations.
Parallel title: QUESCREN Working Paper no.1
Keywords: Official Language Minority Community (OLMC)

Les Québécois d'expression anglaise et la fonction publique du Québec - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
Ce document de travail fournit des renseignements contextuels sur la participation des anglophones à la fonction publique du Québec (FPQ). La première partie fait la synthèse de l’information pertinente recueillie auprès de sources primaires et secondaires. La seconde offre un résumé de nos discussions exploratoires avec des personnes-ressources clés, suivi de nos observations.
Parallel title: Document de travail QUESCREN no.1
Keywords: Official Language Minority Community (OLMC)